The soul of a horse : life lessons from the herd - Camp, Joe. frey50 (New York : Three Rivers Press, 2008)
A surprise birthday gift plunged Joe Camp and his wife, Kathleen, into the world of horses as complete neophytes without a clue as to what horses needed or wanted. The Camps went searching for logic and sense in the rule books of traditional horse care, and what they found was not what they had expected. This memoir leads us on a voyage of discovery as Joe and Kathleen navigate uncharted, often politically incorrect territory on their way to achieving a true relationship with their horses. As the creator of the Benji series, Joe has spent most of his life luring us into the heart and soul of a famous dog, but now he deftly lures us into the heart and soul of a horse. In doing so, he exposes astonishing truths that apply not only to horses but to life and to people as well.--From publisher description.
"Originally published in hardcover in the United States by Harmony Books ... in 2008." -- T.p. verso.
Keywords: Horses; Human-animal relationships